Applications of medicinal chemistry for drug discovery against Acanthamoeba infections - Usman, Ahmed *; Ayaz, Anwar *; Ong, Seng Kai *; Areeba, Anwar; Khan, Naveed Ahmed (Wiley, 2022)
Acanthamoeba is a genus of free-living amoebae, pervasively found in the environment. Most of its pathogenic species are the causative agent of sight-threatening Acanthamoeba keratitis and fatal granulomatous amoebic encephalitis. Despite the advancements in the field of chemotherapy, treating Acanthamoeba infections is still challenging due to incomplete knowledge of the complicated pathophysiology. In case of infection, the treatment regimen for the patients is often ineffective due to delayed diagnosis, poor specificity, and side-effects. Besides the resistance of Acanthamoeba cysts to most of the drugs, the recurrence of infection further complicates the recovery. Thus, it is necessary to develop an effective treatment which can eradicate these rare, but serious infections. Based on various computational and in vitro studies, it has been established that the synthetic scaffolds such as heterocyclic compounds may act as potential drug leads for the development of antiamoebic drugs. In this review, we report different classes of synthetic compounds especially heterocyclic compounds which have shown promising results against Acanthamoeba. Moreover, the antiamoebic activities of synthetic compounds with their possible mode of actions against Acanthamoeba, have been summarized and discussed in this review.